2022
DOI: 10.3389/fenvs.2022.936648
|View full text |Cite
|
Sign up to set email alerts
|

Research on the impact of digital inclusive finance on rural human capital accumulation: A case study of China

Abstract: The accumulation of rural human capital is one of the important factors to realize the sustainable development of the rural economy. Digital inclusive finance eases the budget constraints of farmers and affects their willingness and ability to invest in education which improves human capital accumulation. The impact of digital inclusive finance on rural human capital accumulation is strong but complex to determine. Based on the data from 31 provinces of China from 2011 to 2020, this study uses the systematic G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The more advanced the level of rural human capital, the more effective the construction of digital villages becomes in advancing the development of rural industrial integration. The result is consistent with the research results of human capital (11,15,50). Given the population outflow in rural areas of China, specifically the youth's migration to urban centers, we confront a growing issue of aging and a dearth of technological literacy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The more advanced the level of rural human capital, the more effective the construction of digital villages becomes in advancing the development of rural industrial integration. The result is consistent with the research results of human capital (11,15,50). Given the population outflow in rural areas of China, specifically the youth's migration to urban centers, we confront a growing issue of aging and a dearth of technological literacy.…”
Section: Discussionsupporting
confidence: 88%
“…In the digital era, human capital emerges as a crucial factor shaping a regional "digital capability divide" and elucidating the impacts of digital empowerment (47)(48)(49). Although digital technology integration into real sectors could potentially stimulate knowledge spillovers, fostering the development of rural human capital (24,50,51), the effects of digital technology diffusion and application in rural areas remain limited. This limitation is largely due to the ongoing "hollowing out" of rural areas in China, in other words, the loss of younger populations due to depopulation or urbanization, which exacerbates the loss of rural human capital.…”
Section: Human Capital Heterogeneity In the Digital Village-empowered...mentioning
confidence: 99%
“…Inclusive finance bridges the shortcomings of traditional finance, providing not only accessible, affordable, comprehensive and sustainable financial services for the disadvantaged groups who lack financial options, but also more extensive, convenient and affordable financial services for the general population; it not only expands the breadth of financial services coverage, but also extends the depth of high-quality financial services. Its ultimate goal is to support the economic growth of enterprises and households, eliminate poverty and inequality, and expand the scope of financial services so that all groups can receive appropriate financial services that match their own needs, which is a dynamic and changing guide for action and reflects the value pursuit of financial activities [62][63][64][65][66][67]. However, the cost of risk identification, credit records and data acquisition for inclusive finance is high, and the general approach adopted by traditional inclusive finance is often difficult to balance the endogenous requirements of accessibility, affordability, comprehensiveness and commercial sustainability, so for inclusive finance to achieve long-term development, it also needs to find a new breakthrough, so the technology based on digital technology, mobile Internet, cloud computing, artificial intelligence, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have found that digital financial inclusion plays an important role in rural revitalization. Digital financial inclusion helps to alleviate credit constraints of farmers (FAN, 2021), and reduce their vulnerability (Wang and He, 2020); helps to narrow the urban-rural gap (Ji et al, 2021;Yu and Wang, 2021;Zhao et al, 2022), play an important role in rural economic development (Chen and Zhao, 2021); help promote the accumulation of rural human capital (Li et al, 2022), improve the level of agricultural green development (Guo et al, 2022). There are some results about the role of digital financial inclusion on the environment, e.g.…”
Section: The Environmental Effects Of Financial Development "Battle"mentioning
confidence: 99%